The experimental study of effect of grinding process on thermal and surface roughness - Mohd Helmi, Abd Jalil (2010)
Grinding is one of the important finishing machining operation. It is applied at the last stage of manufacturing process so that the high dimensional accuracy and desirable surface finish product can be achieved. However, there is a lot of problem occur in order to achieve the high dimensional accuracy and desirable surface finish. For examples, surface burning due to excessive heat produce and undesirable surface finish outcomes. The work presented in this paper aims at evaluating the surface temperature after grinding as well as the surface finish of the Stainless Steel AISI 304 grinds with Aluminium Oxide wheel by study the effect of the independent variable such as depth of cut (μm), table speed (m/s), and grinding passes. This experiment is held in two conditions which are dry and wet grinding with every condition is 18 runs of experiments. Soluble oil is used at wet grinding. The grindability results have shown that while dry grinding generates higher surface temperature and higher surface finish of the Stainless Steel workpiece rather than wet grinding. In comparison with independent variables, it is found that, the depth of cut can be labelled as the predominant effect to the rise of surface temperature and higher surface roughness of the Stainless Steel workpiece for both conditions. At the constant depth of cut, varied table speed and grinding passes, it is found that at the lowest table speed will generate higher surface temperature and smoother surface roughness for both of the experiments. In the case of grinding passes, higher surface temperature and smoother surface roughness is generated at the higher number of grinding passes for both the experiments. By the end of the thesis, grinding in wet operation, with lowest depth of cut (10 μm), minimum table speed (10 m/s) and higher grinding passes (2 passes) are recommended to grind Aluminium Oxide wheel with Stainless Steel AISI 304 to obtain the satisfied surface temperature (30.4 oC) and surface roughness (1.433 μm).